SMG-YOLO: PCB Defect Detection Algorithm Based on Improved Multiscale Fusion Optimization with YOLOv11n - Liang, Haojun; Yang, Dazhi; Zhang, Yingqian (International Journal of Computer Science and Information Technology, 2025)
Printed Circuit Board (PCB) is the substrate of electronic parts, the demand is great, carrying the layout of the circuit components and wires, and its good or bad on the quality of electronic products has important impact! To address the limitations of insufficient detection accuracy and suboptimal real-time performance in current PCB surface defect detection methodologies, this study proposes SMG-YOLO, an enhanced YOLOv11n architecture. The proposed framework integrates three principal innovations: 1) a multi-scale fusion convolution module (MSCB) synergistically combined with C3k2 blocks to optimize feature extraction across spatial resolutions; 2) replacement of the conventional Neck structure with a hierarchical SlimNeck architecture to enhance computational efficiency; and 3) implementation of a Global Context Aggregation mechanism to refine defect localization precision. Experimental validation demonstrates that SMG-YOLO achieves state-of-the-art performance metrics, including a mean average precision (mAP50) of 95.5% and a recall rate of 97.0%, surpassing the baseline YOLOv11 model by 4.3% and 2.0%, respectively. Furthermore, the optimized architecture attains a Computational amount of only 7.7 GFLOPs and a processing speed of 232.8 FPS, satisfying stringent industrial requirements for high-throughput inspection.